Assessment of Alkaline Phosphatase, Salivary Flow Rate and Salivary Potential of Hydrogen in Relation to Severity of Chronic Periodontitis - Hussein A. Mousa; Saif S. Saliem (College of Dentistry/ University of Baghdad, 2016)
Background: The cells of periodontium contain many intracellular enzymes like (alkaline phosphatase ALP) that are released outside into the saliva and gingival crevicular fluid (GCF) after destruction of periodontal tissue. The aim of study was to determine the activity of this enzyme in saliva and its relation to the salivary flow rate, PH and clinical periodontal parameters in patients with chronic periodontitis. Subject, Materials and methods: Sample population consist of 75 individuals ;divided into four groups , the first group (15):control subject, the second group (20):mild chronic periodontitis, the third group(20) moderate chronic periodontitis and the fourth group (20) sever chronic periodontitis, Measurements of plaque index (PLI), gingival index (GI), bleeding on probing (BOP), probing pocket depth (PPD) and clinical attachment level (CAL), only male were included and saliva was collected from them and subjected to biochemical analysis of the alkaline phosphatase enzyme (ALP), and also measurement of salivary flow rate(FR) and PH. Results: Statistical analysis of the results revealed the presence of a highly significant difference in the enzymatic activity between healthy and chronic periodontitis subjects (mild, moderate, severe) with positive correlation between the activity of this enzyme and the clinical periodontal parameters, and negative correlation between this enzyme and Salivary flow rate and pH. Conclusion: From this study it can be concluded that a number of markers show promise as sensitive measures of disease and the effectiveness of therapy. At this time enzymes such as alkaline phosphatase ALP, is good biochemical markers of screening chronic periodontitis. Also ALP can be used as a monitor for healthy individuals and patients with different periodontal diseases. Furthermore, analysis of saliva may offer a cost effective approach to assessment in controlling progression of chronic periodontitis in large populations.